Change Management: A Change Everyone Fears? (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Change Management is often defined as a structured approach to transitioning individuals, teams and organisations from a current to desired future state, aimed firstly at employee empowerment for accepting that change. But that change inevitably brings fear: fear of being unable to adapt, fear of meeting or working with new people, fear of a new workplace or even new tasks that will be given. It is an evolutionary fear that brings resistance to everything that changes routine in our lives. The goal of this paper is to show, using a survey which will collect data of Croatian employees who have come across those changes, different perspectives and barriers which those fears bring and that they are possible to overcome even in the earlier stages of change management projects in order to become much more effective in our workplaces.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.